Development of a list of high-risk perioperative medications for the elderly: a Delphi method. Issue 9 (2nd September 2019) - Wang, Ke; Shen, Jianghua; Jiang, Dechun; Xing, Xiaoxuan; Zhan, Siyan; Yan, Suying
ABSTRACT: Objectives : There is a lack of direct evidence for the management of perioperative medications in elderly patients. Therefore, the authors aimed to develop a list of high-risk medications for the elderly population in China to provide indicators for clinicians to identify medication-related factors contributing to potential adverse events during the perioperative period. Methods : The initial list of high-risk perioperative medications was developed by studying all the publications that described specific high-risk medications and their risk profiles in the elderly. Delphi consultations were performed to form a consensus among the group of experts and the list was finalized. Results : The expert panel consisted of 36 experts from 29 tertiary hospitals and 18 provinces or municipalities. The consensus was reached after two Delphi rounds. Finally, a total of 86 medications of 13 medication classes and 120 screening items were included in the final list, along with perioperative risk profiles and risk aversion recommendations for each drug. Conclusion : This is the first study to establish a high-risk perioperative medication list in China, which can be used as a reference for intervention and evaluation of perioperative medications for the elderly population.